Assessment methodology for Lean Practices in healthcare organizations: case study in a Brazilian public hospital - Guilherme Tortorella; Byanca Pinheiro Augusto; Sérgio Luiz Braga França; Rapinder Sawhney (Production)
Abstract Paper aims This article aims at proposing a methodology for assessing lean practices in healthcare organizations that are undergoing a lean implementation. Originality The proposed methodology evaluates healthcare organizations and help managers identify the relationships intensities between their problems and lean practices. This application occurs in a case study in an Emergency Department from a Brazilian public hospital. Research method The proposed methodology provides a theoretical framework that addresses lean practices according to fundamental aspects of the organization, such as people, partnerships, results, processes and leadership, corroborating to a systemic view of lean implementation and facilitating its long-term sustainability. Main findings Our findings provide guidelines for the public hospital leadership, allowing a clear focus on the improvement efforts that can mitigate problems. Implications for theory and practice Due to contextual diversity, the understanding of the critical success factors for lean implementation under such conditions deserves attention. Hence, the proposed method allows practitioners and academics to better comprehend the lean implementation within healthcare organizations. Such enhanced comprehension allows to anticipate potential issues throughout the lean implementation, entailing more assertive efforts. Moreover, accounting for specific problems when designing the lean implementation avoids the utilization of a general and ineffective approach.